Comparison of Quality of Life of Mothers and Fathers of Children with Autism, Baghdad 2024 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The following essay will provide a concise overview of the existing literature on the subject.Autism is a neuropsychiatric developmental syndrome that manifests before the age of three. The common features of these disorders are difficulties in acquiring cognitive, linguistic, social, and motor skills. Consequently, many parents of children with autism are confronted with additional challenges, including stigma and psychological distress, such as stress and depression, arising from their child's behaviour. Consequently, the presence of an autistic child in a family is hypothesised to have a detrimental effect on the parents' quality of life.Objectives:     The primary objective is to assess and compare the quality of life of mothers and fathers of children with autism and to explore the association of quality of life with some sociodemographic features.Subjects and methods:A cross-sectional study was conducted on 200 parents of children with autism from 1st February to 1st August 2024. The study included 100 fathers and 100 mothers at the Children Welfare Teaching Hospital, the Central Teaching Hospital of Pediatrics, and the Baghdad Autism Department. Data from the questionnaire was analysed to determine the quality of life of both parents with a child with autism. The data was collected through direct interviews with all participants using the World Health Organization Quality of Life Scale (WHOQOL-BREF), which comprises four main domains: physical, psychological, social, and environmental. The inclusion criteria were as follows: Iraqi parents of children with autism who were willing to participate in the study and parents with an autistic child who had received a diagnosis of at least six months. The exclusion criteria were as follows: parents of children with other psychiatric or neurological disorders and parents with psychological problems or disability.The results of the study are as follows:With regard to the quality of life of parents, the mean total quality of life score for the group of fathers included in the study was 40.63 ± 3.3, while for the mothers, it was 41.18 ± 4.1. The mean total QoL score for the included parents was 40.91 ± 3.8. The distribution of total QoL among the fathers was found to be poor in 37% of cases and moderate in 63%, while among the mothers, it was found to be poor in 33% of cases and moderate in 67%. The distribution of QoL among the included parents was found to be poor in 35% of cases and moderate in 65%. The environment and psychological domains exhibited the most significant mean impacts on both the included fathers and mothers.The association between the World Health Organization Quality of Life - BREF domains and the demographic data of the included children and parents revealed statistically significant better quality of life for the physical domain with child age, duration since diagnosis, parent age, and marital status. A statistically significant association was identified between the duration since diagnosis and the psychological domain of the WHOQOL-BREF.Conclusion:The study's findings indicate that the quality of life of parents of autistic children is moderately impacted. The study identified several factors that contributed to this effect, including child age, duration since diagnosis, parent age, and marital status.